A questionnaire for rating health-related quality of life - Janković Slobodan M.; Bogavac-Stanojević Nataša; Mikulić Iva; Izetbegović Sebija; Iličković Ivana; Krajnović Dušanka; Suljic Mehmedika Enra; Gojak Refet; Mehičević Admir; Gazibera Belma; Mahmutbegović Nevena; Stojadinović Milorad; et al. (Sciendo, 2021)
Translations of instruments for measuring quality of life developed in certain, mostly more developed, parts of the world usually do not cover regionally specific aspects of health-related quality of life, even after transcultural validation. The aim of this study was to develop and validate a reliable questionnaire in Serbian, Croatian, Bosnian, and Montenegrin languages suitable for measuring health-related quality of life in adults.